Regional Geography Teaching in Terms of the Philosophy of Social Sciences in Universities in Turkey - (:unkn) unknown (MARMARA UNIV, 2016)
Regional geography is a subfield of geography which dominated the discipline between the second half of the 19th and the first half of the 20th century. During this period, the world and countries were divided into specific regions according to geographical features and then regions were examined based on those features. After the Second World War, regional geography ceased to be a main paradigm in geography. It was replaced by other paradigms being mostly positivist. Although region was moved away from the geographical discipline central point, the term of region, remained to be in use widely in the discipline. Currently, most universities in Turkey have continued to teach widely the seven-region concept of geography created by the First Geography Congress of Turkey in 1941. This regional dividing is not compatible with existing geographical understanding. It does not reflect the reality by creating inexplicable borders, and did not undergo any significant change after their setting. Regional geography criticized for displaying essentialist approach and being reductionist and it was questioned why regional borders drawn this way. For these reasons it is difficult to find a common ground between approaches in philosophy of social sciences and the regional geography having unchangeable borders.
Keywords: Regional geography; geography teaching; reductionism; essentialism; philosophy of social sciences